Found after 60 years: the hows and whys of Sphaeromides virei montenigrina (Crustacea: Isopoda: Cirolanidae) rediscovery in Obodska pećina, Montenegro - Teo Delić; Boris Sket (Natura Sloveniae)
Despite being the biggest isopod crustacean in Dinarides, little is known about the genus Sphaeromides and its taxonomical status. Sphaeromides virei montenigrina, one of the three subspecies, has been known only thanks to a female specimen found and described in the late 1950s. Despite the intensive search, almost 60 years were needed to discover additional specimens in the cave Obodska pećina, Montenegro. In this study we present a review of the possible reasons for this long lasting search.